X-men: age of apocalypse: twilight ebook - Bedard, Tony (X-Men: Age of Apocalypse., 2024)
X-Man #53-54; X-Men: Age of Apocalypse #1-6; Exiles (2001) #60-61; What If? (1989) #77, 81; What If? X-Men Age of Apocalypse #1 and material from X-Men: Age of Apocalypse One-Shot, Hulk: Broken Worlds #2, X-Men Prime, X-Men: Endangered Species, Exiles: Days of Then and Now #1, Official Handbook of the Marvel Universe: X-Men - Age of Apocalypse 2005. When reality was restored, what happened to the Age of Apocalypse? Find out right here! With Apocalypse destroyed, surely it’s happy ever after for Magneto and his X-Men? Not if Sinister has his way! Blink and Sabretooth revisit their home dimension, dragging the Exiles along for the ride, while a little piece of home finds Nate Grey, exiled in the Marvel Universe! And don’t forget the Dark Beast and the AoA Hulk! Plus: What if things happened very differently